DOES THE SHADOW ECONOMY AFFECT FOREIGN DIRECT INVESTMENT? CASE STUDY OF POLAND AND POLISH REGIONS - Andrzej Buszko (Polityki Europejskie, Finanse i Marketing)
The main goal of the research was to identify the relationship between the level of shadow economy and Foreign Direct Investment. The research was carried in Poland and Polish regions during 1990-2020. MIMIC approach was employed to calculate the level of shadow economy as a % of Polish and regional GDP. Pearson correlation index and Kolmogrov-Smirnov test were applied as well. The study proved there is a sound negative correlation (-0,636) between the shadow economy and foreign direct investment in Poland, but regional associations between those two variables demonstrated different results. Unlike in other Polish provinces, in Opolskie and Podkarpackie the correlation index confirmed a positive association between the level of shadow economy and FDI flow.